The unseen protagonists. Ecuadorians’ daughters between Ecuador and Southern Europe - Lagomarsino, F.; Castellani, S. (Social Identities, 2016)
Scholars consider Latin American migration toward Europe to be a case study in the feminization of international migration. However, these studies have not focused on second-generation girls. Beginning from a gender and intergenerational approach, this paper stresses the agency role played by the reunified teenage daughters of Ecuadorian migrants both in Ecuador as well as in Southern Europe. The discussion is based on two transnational ethnographic studies conducted with Ecuadorian children aged 13-18 and their families in two medium-sized Southern European cities, Genoa and Seville, and in Ecuador between 2008 and 2011. First, the paper shows that girls carry out an essential task as caretakers in the transnational household, both in the point of origin and destination. Despite these responsibilities, they show a higher commitment to school, both in terms of time spent in school and their results. Secondly, it analyses how girls negotiate their role both inside and outside of the family, challenging the parents' moral and sexual control strategies. The results disclose an identity struggle in the everyday lives of these girls: they participate in the migration project of the transnational family, but simultaneously they implement practices of resistance and renegotiation addressing the traditional division of gender roles.